Persepsi Mahasiswa terhadap Pelaksanaan Perkuliahan Naḥwu dengan Sistem Daring - Muhammad Jundi (Al-Ma‘rifah, 2020)
This article aims to describe students’ perceptions of naḥwu 2 lecture with online system for 4th-semester students in the Arabic Language Department, IAIN Sultan Amai, Gorontalo. The study was conducted in a survey type with a qualitative approach. The data collection techniques used were questionnaires and interviews. Data were analyzed using qualitative data analysis techniques by Milles and Huberman, including data collection, data reduction, data presentation, and concluding. Research results: (1) Online lecture for naḥwu 2 is carried out with deductive methods in the form of lectures, memorizing Matn al-Ājurrūmīyah, and group material presentation; (2) As many as 46.15% of respondents stated that the material was not well presented. The influencing factors are group presentation and network quality. Only 53.85% of respondents stated that the understanding they got after attending naḥwu 2 lectures online was quite good. As many as 84.62% of respondents stated that memorization of the matn had a positive effect on understanding the material and the ability to take words. According to them, online lecture are considered ineffective in naḥwu 2. The retention of the material they get is not comparable to the funds they spend on internet quota needs during naḥwu 2 online lecture.